«Introduction: The Impact of the Great Recession and the Commodity Crisis upon Political Representation in Southern Europe and Latin America» - Freire, A.; Mélany Barragán; Coller, X.; Lisi, M.; Tsatsanis, E. (Political representation in Southern Europe and Latin America. Before and After the Great Recession and the Commodity Crisis., 2020)
André Freire, Mélany Barragán, Xavier Coller, Marco Lisi & Emmanouil Tsatsanis (2020); «Introduction: The Impact of the Great Recession and the Commodity Crisis upon Political Representation in Southern Europe and Latin America», in André Freire, Mélany Barragan, Xavier Coler, Marco Lisi & Emmanouil Tsatsanis (editors) (2020), Political representation in Southern Europe and Latin America. Before and After the Great Recession and the Commodity Crisis., Edited volume for Routledge book series “Routledge Research on Social and Political Elites”, 2020.